Keragaman Genetik Ikan Beronang (Siganus) dan Ikan Cobia (Ranchycentron Canadum) Dari Indonesia dan Taiwan - Jin Chywan Gwo; Yudha Trinoegraha Adiputra; Te Hua Hsu (Inovasi Pembangunan : Jurnal Kelitbangan, 2018)
Genetic diversity of rabbitfish (Siganus) and cobia (Ranchycentron canadum) from Indonesia and Taiwan was compared. Rabbitfish was fisheries commodities and cobia was cultured in Taiwan and Indonesia. Study aimed to compared genetic diversity of both species as a references for conservation and culture species. Finger printing DNA method were AFLP (amplified fragment length polymorphism) within two primers use to assesed their diverence. Multivariate analysis was used to amount statistical similarities within DNA fragments of AFLPs. Results showed there is two different species of rabbitfish within Hurun Bay of Lampung were Siganus fuscescens dan S.gutattus. Indepth analysis also shown rabbitfish from Taiwan was different with Indonesia showed by genetic distance. These results showed there is no relation within ancestor of rabbitfish from this two locations.Contrast with cobia, Taiwan stocks seperated in two groups and one of Indonesia group joined with Taiwan group and the other independently. These results showed cobia from Indoneisa only limited population of cobia from Taiwan. This study recommended rabbitfish from Hurun Bay of Lampung was pure and genetically approved as cultue fish species. Indonesia may use other cobia stocks from Taiwan, in case there is inbreeding depression threats the established Indonesia cobia stocks.